Analisis Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Pemerintah Kabupaten Bondowoso Tahun 2018-2022 - Nur Cahyo, Putro (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
The objective of the study is to assess the performance of budget realization concerning regional income and expenditure in Bondowoso Regency from 2018 to 2012. The research relies on secondary data obtained from the annual financial reports of Bondowoso Regency's Regional Budget (APBD) spanning from 2014 to 2018. Employing a qualitative descriptive analysis method, the study primarily focuses on the Budget Realization Report (LRA), particularly emphasizing expenditure analysis. The findings of the study reveal that expenditure recorded in the LRA for the years 2014-2018 indicate commendable performance by the Bondowoso Regency Government, showcasing continual enhancements in expenditure utilization annually. Noteworthy expenditure growth was observed in 2016 compared to the years 2014-2015. Consequently, it is recommended that in subsequent years, the Bondowoso Regency Government ensures a balanced allocation of regional resources in line with the requirements of regional development and community welfare. Such allocation of regional expenditure is expected to enhance future spending effectiveness, productivity, and efficiency.